Key determinants of university dropout: academic, economic, and psychosocial factors in student retention - Valencia-Arias, Alejandro; Valera Aredo, Julio César; Valencia, Jackeline; Cardona-Acevedo, Sebastián; Patiño-Vanegas, Juan Camilo; Uribe Bedoya, Hernán (Frontiers in Education, 2026)
IntroductionUniversity dropout remains a persistent challenge in higher education, reflecting structural tensions between inclusivity, student retention, and educational equity. Rather than approaching dropout as a simple aggregation of causes, this study adopts a comprehensive perspective that integrates academic, economic, and psychosocial dimensions, emphasizing their interaction with institutional contexts and responses.MethodsA systematic literature review was conducted following the PRISMA 2020 guidelines. Nineteen empirical studies were selected and analyzed to identify the main determinants of university dropout, as well as the institutional strategies and theoretical models used to understand and prevent student attrition. Data were synthesized through a comparative and thematic analysis, focusing on the frequency and articulation of determinants across studies.ResultsThe analysis indicates that motivation (73.7%), academic performance (57.9%), and financial hardship (31.6%) are the most recurrent determinants of dropout. Psychosocial factors, particularly emotional well-being and social integration, also show a substantial influence on student retention. In terms of institutional responses, predictive analytics, early warning systems, and comprehensive student support programs emerge as the most effective strategies for identifying at-risk students and reducing dropout rates.DiscussionCompared with prior reviews, the findings reveal limited theoretical integration and methodological consistency, as most studies focus on isolated variables without adequately linking them to broader institutional frameworks. The evidence highlights the need for multidimensional and theoretically grounded approaches that connect academic, economic, and psychosocial factors with coordinated institutional action. Such frameworks are essential for strengthening student retention strategies and advancing equity in higher education.